Autonomous Real-Time Mass Center Location and Inertia Identification for Grappling Space Robotics - Timothy Sands (Technologies)
Grappling actions by space robots for the purposes of stabilizing, refueling, repair, and equipment replacement necessitate the autonomous abilities of a single grappling space robot to rapidly contend with large variations in total system inertia rapidly shifting a system’s center of mass, as targets can be massive with possibly unknown or poorly known mass inertia properties. Grappling actions yield opportunities for a novel online calculation of the time-varying location of the combined system’s center of mass. Two-norm optimal nonlinear, projection regression-based learning is implemented and juxtaposed to a comparative benchmark both qualitatively and quantitatively supported by a comparison of enhancements of Luenberger observers. Analysis precedes modeling and simulation to verify the design, and then, spaceflight experiments are proposed for the sequel to validate the simulation results. Time-varying mass locations are discerned, and the time-varying location of the mass center is revealed to be 36–95 percent different than initially assumed, and 58–317 percent corrections to inertia identification are demonstrated. Combined three-dimensional maneuvers obscures identification compared to single-axis maneuvering.